Disrupting dark web supply chains to protect precious data. Issue 4 (April 2019) - Wilson, Emily
Abstract : In our digital-centric, always-on, cloud-powered world, data is your organisation's biggest asset. Whether it's sensitive customer information, intellectual property (IP) or closely guarded financial and other corporate data, it might already be up for sale on the dark web. Cybercrime and online fraud are now easier than ever thanks to these sophisticated underground markets. Data is your organisation's biggest asset. But whether it's customer information, intellectual property or financial and other corporate data, it might already be up for sale on the dark web.